1977
DOI: 10.1111/j.1095-8649.1977.tb04124.x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance of Gambusia affinis (Baird & Girard) and Heteropneustes fossilis (Bloch)

Abstract: The present paper describes the results of a study on the salinity tolerance of two freshwater fishes, Gambusia aftinis (Baird & Girard) and Heteropneustes fossilis (Bloch). The two species were treated with various concentrations of sea water and three most common salts found in the saline waters of Iraq, namely sodium chloride, calcium chloride and potassium chloride. The mortality rates following these treatments were recorded. Both species showed the highest degree of resistance for sea water and sodium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…They generally exhibit wide tolerances, e.g. Gambusia affinis can tolerate 59000 mg L -' for 30 days (Chervinski, 1983), with a 4-day unacclimated LC,, of 15000 mg L-' (Al-Daham & Bhati, 1977).…”
Section: Melanotaeniidaementioning
confidence: 99%
“…They generally exhibit wide tolerances, e.g. Gambusia affinis can tolerate 59000 mg L -' for 30 days (Chervinski, 1983), with a 4-day unacclimated LC,, of 15000 mg L-' (Al-Daham & Bhati, 1977).…”
Section: Melanotaeniidaementioning
confidence: 99%
“…Singi fish can survive in m e d i a w h i c h are considerably h y p e r t o n i c to its n a t ural fresh w a t e r h a b i t a t containing about 5 m O s m sal i n i t y (A1 Dah a m and Bhatti, 1977;P arwez et at., 1979). In some r e p r e s e n t a t i v e e x p e r i m e n t s w e hav e found that they also survive »+5-50 days in d i s t i l l e d w a t e r but on ly 12-16 days in 270 m O s m NaCl medium, this o s m o l a r i t y is about the same as that of its b o d y fluid (Parwez et at.…”
Section: Discussionmentioning
confidence: 99%
“…Since the fresh w a t e r fishes are h y p e r t o n i c to the s u r r o u n d i n g w a t e r , t h e i r body organs are also likely to be a f f e c t e d o r influen-ced by the change in osmotic c oncentration of the m e d i u m . T h e salinity t o l e ran c e of Singi fish (He t e r opneustes fossilis Bloch), a stenoh a l i n e fish, has been reported (A1 Daham and Bhatti, 1977;Parwez et a l . , 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Cold-tolerant G. affinis from Utah can survive temperatures above 0.5°C when acclimated to 5-10°C water, and G. affinis from Indian Hot Springs, Arizona have a lower lethal limit of 2.7°C when acclimated to 5-10°C (Otto 1973;Al-Daham and Bhatti 1977;Lynch 1988;Meffe and Snelson Jr. 1989).…”
Section: Stressor Descriptionmentioning
confidence: 95%
“…Gambusia affinis can grow to a maximum length of 49 mm in 36-75 days depending on environmental conditions, and can tolerate salinities of up to 50% sea water (Krumholz 1948;Al-Daham and Bhatti 1977). Cold-tolerant G. affinis from Utah can survive temperatures above 0.5°C when acclimated to 5-10°C water, and G. affinis from Indian Hot Springs, Arizona have a lower lethal limit of 2.7°C when acclimated to 5-10°C (Otto 1973;Al-Daham and Bhatti 1977;Lynch 1988;Meffe and Snelson Jr. 1989).…”
Section: Stressor Descriptionmentioning
confidence: 99%